Big Data, Cloud Computing, Data Science & Engineering - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the outcomes of the 3rd IEEE/ACIS International Conference on Big Data, Cloud Computing, Data Science & Engineering (BCD 2018), which was held on July 10-12, 2018 in Kanazawa. The aim of the conference was to bring together researchers and scientists, businesspeople and entrepreneurs, teachers, engineers, computer users, and students to discuss the various fields of computer science, to share their experiences, and to exchange new ideas and information in a meaningful way. All aspects (theory, applications and tools) of computer and information science, the practical challenges encountered along the way, and the solutions adopted to solve them are all explored here. The conference organizers selected the best papers from among those accepted for presentation. The papers were chosen on the basis of review scores submitted by members of the program committee and subsequently underwent further rigorous review. Following this second round of review, 13 of the conference's most promising papers were selected for this Springer (SCI) book. We eagerly await the important contributions that we know these authors will make to the field of computer and information science.
Chapter 1. Designing a method of data transfer using dual message queue brokers in an IoT environment (Hyun-Seong Lee) -- Chapter 2. Bluetooth Low Energy Plate and PDR Hybrid for Indoor Navigation (Hee-Yong Kang) -- Chapter 3. A Study on the Common Collaboration Platform Activation of Cloud-based Manufacturing Supply Management System (SCM) (Sanhae Kim) -- Chapter 4. Service Management and Model Driven Management (Haeng-Kon Kim) -- Chapter 5. Measuring the Effectiveness of E-Wallet in Malaysia (Faisal Nizam) -- Chapter 6. Designing of Domain Modeling for Mobile Applications Development (Haeng-Kon Kim) etc.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence